Cusp repair during aortic valve-sparing operation. Issue 4 (April 2015) - Settepani, Fabrizio; Cappai, Antioco; Raffa, Giuseppe M.; Basciu, Alessio; Barbone, Alessandro; Berwick, Daniele; Citterio, Enrico; Ornaghi, Diego; Tarelli, Giuseppe; Malvindi, Pietro G.
<x xml:space="preserve">Abstract</x> Aims Aortic valve-sparing operations are nowadays considered safe and reliable procedures in terms of mid-term and long-term results. Although surgical techniques regarding the modality of grafts' implantation have been properly addressed, the modality of cusp repair, when needed, is still open to debate. We sought to review the literature to try to shed light on when the cusp repair is required and how it should be performed. Methods We searched the PubMed database using the keywords aortic valve-sparing operation, aortic valve-sparing reimplantation, valve-sparing aortic root replacement, aortic valve repair, and aortic cusp repair. Only studies that included and described in detail the technique of cusp repairs in adjunct to aortic valve-sparing operation were considered. Results Bicuspid aortic valve more often requires correction when compared with tricuspid valve. The range of the techniques varies from the 'simple' free margin plication to the more complex triangular resection with patch repair. Results in the literature seem to be encouraging, showing that, in most of the cases, cusp repair does not affect valve competence in the mid-term and long-term. Conclusion Correction of the cusp is a delicate balance between undercorrection that could lead to residual prolapse and overcorrection that could lead to cusp restriction. Although complex repair of the aortic valve in addition to root replacement provided satisfactory results, it should be reserved for experienced centers with a large volume of patients.